Influencia de la hipoxia sobre el metabolismo óseo. Rol central del factor inducible por hipoxia - Aguirre Siancas, Elías Ernesto (2013)
Knowledge of hypoxia influencing human physiology determined discovery of hypoxia-inducible factor (HIF). Regulation of molecules by this transcription factor is varied and complex and understanding continues on. Several processes like ossification, remodeling and repair occur in bone tissue physiology and pathophysiology. Decrease in available oxygen determines HIF stabilization in many cell groups, standing out osteogenic lineage cells. This factor regulates expression of multiple genes, the most important perhaps the vascular endothelial growth factor (VEGF) due to its implication in the osteogenic process, directly activating osteoblastic cells or indirectly through potent angiogenesis. In this article, we review HIF central role on bone physiology, detailing regulation of key molecular pathways dependent of this transcription factor.